Study on Kalina Cycle Performance Under Operating Temperature Variations for Ship Waste Heat Recovery - Fajri Ashfi Rayhan; Thashya Nabila Aqeela (International Journal of Marine Engineering Innovation and Research, 2026)
Energy inefficiency in marine diesel engines remains a significant challenge due to substantial waste heat losses. This study aims to evaluate the thermodynamic performance of a Kalina cycle for waste heat recovery from a low-speed marine diesel engine under varying operating temperature and ammonia-H2O compositions. A thermodynamic model is developed based on mass and energy balance principles to analyze system behavior across different conditions. The analysis focuses on key performance aspects, including evaporator heat input (Qin), pump work, expander work, thermal efficiency, and energy losses for ammonia concentrations of 30%, 45%, and 60%. The results show that increasing ammonia concentration significantly reduces the required heat input, while expander work decreases with rising condenser temperature due to a reduced enthalpy drop. Thermal efficiency is found to decrease with increasing evaporator temperature, as additional heat input is not effectively converted into useful work, leading to higher irreversibility. The highest efficiency of 11.9% is achieved at 60% ammonia concentration under lower temperature conditions. In contrast, energy losses increase consistently with higher heat input, particularly at elevated temperatures. Overall, the findings demonstrate that optimal system performance depends on a balanced combination of operating temperatures and working fluid composition.